Improvement of Learning Arabic Interest by Using Animation Video in Students’ Junior High School - Nikmatul Makfiro; Anisatu Thoyyibah; Lailatul Mauludiyah (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
Learning interest plays important role in studying. Low interest may affect students’ learning success. The author used animated videos as an Arabic learning platform to determine the use of animated video in learning Arabic, and determine the supporting and inhibiting factors in the use of it in MTs Almaarif 02 Singosari Malang. This study employs a qualitative descriptive method with data collection techniques through observation, interviews, questionnaires, and documentation. The sample is 28 students. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The study results are: (1) this platform can increase students' interest in learning Arabic; (2) the supporting factors include: stimulating students' enthusiasm and motivation; assisting students to learn and memorize; and assisting teachers to present the material; (3) the inhibiting factors are: insufficient student network and internet limitations; not all material can be presented in the form of animated videos; and making animated videos requires sufficient skills